2016
DOI: 10.2967/jnumed.116.172759
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET–Derived Tumor Blood Flow Changes After 1 Cycle of Neoadjuvant Chemotherapy Predicts Outcome in Triple-Negative Breast Cancer

Abstract: Previous studies have suggested that early changes in blood flow (BF) in response to neoadjuvant chemotherapy and evaluated with 15 O-water are a surrogate biomarker of outcome in women with breast cancer. This study investigates, in the triple-negative breast cancer subtype, the prognostic relevance of tumor BF changes (DBF) in response to chemotherapy, assessed using a short dynamic 18 F-FDG PET acquisition. Methods: Forty-six consecutive women with triple-negative breast cancer and an indication for neoadju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 33 publications
2
22
0
2
Order By: Relevance
“…In this issue of The Journal of Nuclear Medicine, Humbert et al report that low overall survival is associated with triple-negative breast cancer patients whose tumors experienced a less than 30% drop in tumor first-pass BF after neoadjuvant therapy (8). Humbert et al also found their firstpass BF estimates capable of stratifying between patients with 87% versus 48% overall survival (P , 0.001) in women without a pathologic complete response (8). The results of Humbert et al support using first-pass 18 F-FDG PET scans as an alternative to 15 O-water PET scans for estimating BF to tumors.…”
Section: See Page 1707supporting
confidence: 54%
See 2 more Smart Citations
“…In this issue of The Journal of Nuclear Medicine, Humbert et al report that low overall survival is associated with triple-negative breast cancer patients whose tumors experienced a less than 30% drop in tumor first-pass BF after neoadjuvant therapy (8). Humbert et al also found their firstpass BF estimates capable of stratifying between patients with 87% versus 48% overall survival (P , 0.001) in women without a pathologic complete response (8). The results of Humbert et al support using first-pass 18 F-FDG PET scans as an alternative to 15 O-water PET scans for estimating BF to tumors.…”
Section: See Page 1707supporting
confidence: 54%
“…In Humbert et al, results are reported from analyses of a 2-part imaging protocol in which patients were positioned prone followed by a 1-bed-position 18 F-FDG 2-min dynamic PET scan, which was followed by an additional PET scan starting 90 min after injection that was completed over prone patients in a region that included the first scan's imaging area (8) (7) whereas the Humbert et al protocol was completed in patients undergoing neoadjuvant therapy before and after the first course of chemotherapy (8). Analyses of the Humbert et al 2-part set of PET images (2-min dynamic and 90-min static) yielded estimates of BF (first-pass BF from 18 F-FDG scans) and tumor metabolism (SUV) in a manner analogous to the kinetic analysis of a single 60-min dynamic 18 F-FDG scan yielding estimates of tracer transport ( 18 F-FDG transport) and tumor metabolism (flux, metabolic rate of 18 F-FDG, or SUV).…”
Section: See Page 1707mentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor perfusion itself is also a primary variable of interest, because tumor perfusion influences nutrient delivery to the tumor with potential effects on tumor metabolism and progression, and tumor perfusion also affects delivery of chemotherapeutics. Measuring tumor perfusion either at baseline or before and after a therapy cycle has predicted disease-free survival in patients with breast cancer (8,9), response to chemotherapy in head and neck cancer (10), response of cervical cancer to radiation therapy (11), and response of glioblastoma to antiangiogenic therapy (12). In addition to complementing hypoxia reporters and independently providing prognostic data, noninvasive imaging of tumor perfusion could be used preclinically to study strategies for modifying tumor perfusion for either radiosensitization or manipulating chemotherapy delivery.…”
mentioning
confidence: 99%
“…Ultrasound (US) and mammography show moderate sensitivity in the assessment of tumor response. 5 Dynamic contrast-enhanced MRI and 18Ffluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) have been utilized to predict breast cancer response to neoadjuvant therapy, [6][7][8] and have shown their ability in early identification of response. However, MRI and PET/CT are expensive and require injection of contrast agents and their repeated use in monitoring patients during treatment is not feasible.…”
Section: Introductionmentioning
confidence: 99%